Alcohol-related emergency department admissions among adolescents in the Ghent and Sint-Niklaas areas. Issue 5 (3rd September 2015) - Calle, P.; Hautekiet, A.; François, H.; Sundahl, N.; Cornelis, C.; Calle, S.; Damen, J.; Vanbrabant, P.; De Turck, B.; De Graeve, K.; Mpotos, N.; De Paepe, P.
Abstract : Alcohol abuse is a major health concern. The aim of this retrospective study was to analyse the alcohol-related emergency department (ED) admissions among adolescents in all hospitals of distinct areas during a 1-year period. In each hospital, all ED patients with a blood alcohol concentration (BAC) of at least 0.5 g/l were surveyed in a standardised way. Of the 3918 included patients, only 146 (3.7%) were < 18 years. The male-to-female ratio was 1.5:1. There was a strong preponderance of weekend and night time admissions. Most of the patients were transported by ambulance (77% of 138 patients with information on this item). The main reason for ED admittance was depressed level of consciousness (64%), trauma (12%), vomiting and/or abdominal pain (12%), agitation or aggression (4%), syncope (4%) and psychological problems (4%). The context of the alcohol intoxication was related to some kind of festivity in 85%, mental problems in 14% and chronic abuse in 1%. Median BAC values (and range) were 2.08 g/l (0.73–3.70 g/l) for boys and 1.51 g/l (0.73–2.90 g/l) for girls. Most patients (87%) could be discharged home within 24 hours. Our study confirms that problematic alcohol use leading to ED admissions starts in adolescence. Although the numbers of cases below 18 years are low when compared to adults, the phenomenon is alarming as it is associated with substantial health problems. Therefore, Belgium urgently needs a global national alcohol plan, with youngsters being one of the target groups.